A Hybrid Fuzzy AHP-TOPSIS Analysis for Selecting the Optimal Catalyst To Maximize Bio-Oil Yield from Waste Plastics Pyrolysis - Zainulabdeen, Iman Hussein; Tekeli, Fatma Noyan; Figen, Aysel Kanturk (SPRINGER, 2026)
The selection of a suitable catalyst is a critical factor in waste plastic pyrolysis to optimize bio-oil yield. Transitioning to a circular economy offers a sustainable and efficient option by converting plastic waste into alternative energies. This study focuses on selecting the optimal catalyst for maximizing bio-oil yield from catalyst pyrolysis for several types of waste plastics including High-Density Polyethylene (HDPE), Low-Density Polyethylene (LDPE), Polypropylene (PP), Polystyrene (PS), Polyethylene Terephthalate (PET), and Polyvinyl Chloride (PVC) and mixed plastic waste, a critical issue addressed through multi-criteria decision-making (MCDM).The alternatives under consideration are different types of catalysts, with evaluation criteria including catalyst/feedstock ratio, carbon content, hydrogen content, reaction temperature, retention time, and liquid oil yield. We used a hybrid fuzzy analytical hierarchy process (AHP)-technique for order preference by similarity to ideal solution (TOPSIS) to select suitable catalysts, maximize bio-oil yield in catalytic pyrolysis, and rank the catalysts. According to the decision analysis, the catalyst's performance was as follows: Silica-Alumina (alt18) > CuCO3 (alt12) > Zeolite (alt14) > Borax powder (alt16) > TiO2 (alt11) > KOH/AC (alt22) > Novel thermal TA-NZ (alt8). According to the hybrid fuzzy AHP-TOPSIS analysis results, silica-alumina is the most suitable catalyst for polystyrene (PS) pyrolysis. This silica alumina catalyst is made up of zeolite (a molecular sieve), platinum (0.001 wt%), and other matrix components that are active and inactive, as well as a binder. The results revealed that under the extreme conditions tested, a temperature of 410 degrees C and a remarkable bio-oil yield of 97.30% were achieved within a duration of 35 min.
Keywords: Pyrolysis; Waste plastics; Catalyst; AHP-TOPSIS; Multicriteria methods; Bio oil; CONVERSION; FUEL; Environmental Sciences & Ecology